2000
DOI: 10.2214/ajr.174.2.1740549
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Thin-Section CT and Chest Radiography of Pediatric Interstitial Lung Disease

Abstract: A higher proportion of pediatric interstitial lung diseases can be diagnosed on thin-section CT than on chest radiographs. In our study, confident and correct diagnoses were made more frequently with CT than with chest radiographs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 25 publications
2
48
0
7
Order By: Relevance
“…Consequently, the key chest imaging tool for the diagnosis and management of a patient with ILD is HRCT, which can visualise the parenchymal structure to the level of the secondary pulmonary lobule. Recent paediatric literature confirms that HRCT increases the level of diagnostic confidence for infiltrative lung disease [27][28][29][30][31][32]. HRCT has now been proven to be useful for ILD diagnosis in children, and for patient management by helping to select the lung area to be biopsied.…”
Section: Chest Imagingmentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, the key chest imaging tool for the diagnosis and management of a patient with ILD is HRCT, which can visualise the parenchymal structure to the level of the secondary pulmonary lobule. Recent paediatric literature confirms that HRCT increases the level of diagnostic confidence for infiltrative lung disease [27][28][29][30][31][32]. HRCT has now been proven to be useful for ILD diagnosis in children, and for patient management by helping to select the lung area to be biopsied.…”
Section: Chest Imagingmentioning
confidence: 96%
“…In three, HRCT showed a predominantly upper-zone honeycomb pattern with parenchymal distortion superimposed on a background of widespread ground-glass opacification. As discussed in the adult ILD, the presence of ground-glass opacities without HRCT findings of fibrosis may be a marker of an active disease [29,30,[38][39][40]. However, HRCT still needs evaluation as a follow-up tool in paediatric patients.…”
Section: Chest Imagingmentioning
confidence: 99%
“…CXRs are usually the first imaging study performed in chILD syndrome. They rarely provide a specific chILD diagnosis, but they are frequently abnormal, and may identify diseases that mimic chILD syndrome (34,35). CT defines the presence, extent, and pattern of lung disease.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…The observations described here derive from two observational studies that found that CT scanning is more likely than CXR to accurately identify DLD in children (17,35), numerous case series that reported a strong correlation between histologic findings and the thin-section CT scan appearance in children with surfactant protein C mutation (42), neuroendocrine cell hyperplasia of infancy (NEHI) ( Figure 5) (20) and other DLDs (17,19,35), and two studies that demonstrated that CT scanning is superior to MRI in resolution and in identifying ground glass opacity, normal peripheral bronchi, and air trapping in patients with cystic fibrosis (43,44). Although cystic fibrosis is not a chILD disorder, resolution is an important determinant of image quality, and the findings of air trapping and ground glass opacity are key observations in chILD.…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…The chest radiograph is usually very non-specific and non-diagnostic [11]. There may be groundglass shadowing with prominent air bronchograms, or coarse nodular or reticularnodular shadowing; in advanced cases, honeycombing is seen.…”
Section: Imagingmentioning
confidence: 99%